Comparison of the impact of e-cigarettes and new tobacco heating devices on the human body and their potential in the fight against smoking - Kamil Pondel; Kinga Kawałko; Krzysztof Bielewicz; Katarzyna Skowrońska; Patrycja Baciur (Kazimierz Wielki University, 2022)
Nicotine is one of the most common stimulants used by humans in the world. Its addictive potential is almost the same as that of cocaine. [1] The most popular way of delivering nicotine to the body, which is cigarette smoking, has many negative effects, including considerable carcinogenic potential. Cigarette smoke contains approx. 6,500 chemical compounds, of which around 150 are considered toxic. [2] With the advancement of technology, alternative ways of delivering nicotine to the body have been found. These include e-cigarettes and tobacco heaters. In the following study, we will compare the method and mechanism of operation of these devices and their possible effects on human health compared to smoking.